2022
DOI: 10.1186/s12913-022-07703-1
|View full text |Cite
|
Sign up to set email alerts
|

Integrating mental health into primary care: evaluation of the Health Action for Psychiatric Problems In Nigeria including Epilepsy and SubstanceS (HAPPINESS) pilot project

Abstract: Background The Health Action for Psychiatric Problems In Nigeria including Epilepsy and SubstanceS (HAPPINESS) project trains non-specialist and primary health care workers in Imo State, Nigeria. This project adapted the World Health Organization’s Mental Health Gap Action Programme-Intervention Guide (mhGAP-IG), emphasizing stigma reduction among trainees. This convergent mixed-methods proof-of-concept study evaluates the HAPPINESS pilot project mhGAP-IG training’s impact on mental illness sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
2
10
0
Order By: Relevance
“…Results from the pilot implementation of the HAPPINESS intervention showed a high rate of adoption (84%), penetration (service report completion rate of 95%) and fidelity (81%) as well as patient engagement (91%) and retention in care at 12 months (86%). These promising results add to the initial findings of high acceptability and feasibility of the HAPPINESS intervention (Chu et al, 2022). They are also in keeping with other studies of mhGAP-based integration of mental health into primary care in Nigeria and other LMICs (Gureje et al, 2015;Petersen et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results from the pilot implementation of the HAPPINESS intervention showed a high rate of adoption (84%), penetration (service report completion rate of 95%) and fidelity (81%) as well as patient engagement (91%) and retention in care at 12 months (86%). These promising results add to the initial findings of high acceptability and feasibility of the HAPPINESS intervention (Chu et al, 2022). They are also in keeping with other studies of mhGAP-based integration of mental health into primary care in Nigeria and other LMICs (Gureje et al, 2015;Petersen et al, 2019).…”
Section: Discussionsupporting
confidence: 83%
“…Health care workers trainingDetails of the HAPPINESS intervention components, includingTraining, Refresher Training, Clinical Practice, Support Supervision, Community Engagement and the Drug Revolving Fund (Appendix 2 of the Supplementary Material), have been previously published and summarized in Figure 1(Chu et al, 2022). In summary, for the mhGAP-IG training, we chose the following modules: Essential Care and Practice, Depression, Psychoses/Mania, Epilepsy and Substance Use Disorders and made relevant adaptations based on local needs and context.…”
mentioning
confidence: 99%
“…Evidence across a variety health areas and settings has demonstrated that interventions focused on improving the relationship between health workers and clients can effectively increase provider empathy and con dence and improve healthcare utilization and other outcomes [26][27][28][29]. Yet such approaches have not, to our knowledge, yet been widely used in settings such as Nigeria to support provider capacity to deliver a newly introduced self-injectable contraceptive method.…”
Section: Discussionmentioning
confidence: 99%
“…have targeted healthcare workers, rather than community members [24,25]. Further, a systematic review of mental health stigma reduction interventions in low-and middle-income countries found that only a small minority were developed by local residents or culturally adapted [26].…”
Section: Strengths and Weaknesses In Relation To Other Studiesmentioning
confidence: 99%